ANALISIS HUKUM TERHADAP PRAKTIK PRODUK JASA PERBANKAN SYARIAH (FEE BASED SERVICE) - Kasanah, Nur (Inovasi: Jurnal Diklat Keagamaan, 2018)
Islamic bank are the free interest banking in selling their products to earntheir income from profit sharing, margin, administration and fee.Administration and fee are bank’s income from the service sector. Feebased service is the sector which developed by Islamic banks. Newvarious products are issued by Islamic banks under licenced by DewanSyariah Nasional (National Sharia Council). Through Islamic financialengineering method, Islamic banks produce several variety productsthat compatible with sharia principles. Nevertheless, the productsstill refer to the contracts that have been known in Islam such aswakalah, kafalah, hawalah etc. In a fact, there are discrepancybetween regulations and practices in the fields. We found many productsthat are not run based on the rules such as the client’s misunderstandingin sharia contract, the uncompatible fee and some obstacles inapplication of National Sharia Council’s messages.